Acute aortic syndromes: a review of what we know and future considerations. Issue 10 (25th November 2021) - King, R. Wilson; Bonaca, Marc P.
Abstract: Acute aortic syndromes represent a spectrum of life-threatening aortic pathologies. Prompt diagnosis and proper management of these syndromes are important in reducing overall mortality and morbidity, which remains high. Acute aortic dissections represent most of these aortic wall pathologies, but intramural haematomas and penetrating atherosclerotic ulcers have been increasingly diagnosed. Type A dissections require prompt surgical treatment, with endovascular options on the horizon. Type B dissections can be complicated or uncomplicated, and treatment is determined based on this designation. Complicated Type B dissections require prompt repair with thoracic endovascular aortic repair (TEVAR) becoming the preferred method. Uncomplicated Type B dissections require medical management, but early TEVAR in the subacute setting is becoming more prominent. Proper surveillance for an uncomplicated Type B dissection is crucial in detecting aortic degeneration and need for intervention. Intramural haematomas and penetrating atherosclerotic ulcers are managed similarly to aortic dissections, but more research is needed to determine the proper management algorithms. Multi-disciplinary aortic programmes have been shown to improve patient outcomes and are necessary in optimizing long-term follow-up.